Zygmunt Bauman and Physical Education: a path toward new analyses and possibilities (Práxis Educativa, 2025)
This article examines the contribution of Zygmunt Bauman’s work to the field of Physical Education, exploring its relationship with key topics in the area, such as the body, health, fitness, sport, leisure, dance, and play. The study adopts a bibliographic approach based on five selected works and applies Content Analysis to identify recurring themes and their relevance to Physical Education. Parallels are drawn between Bauman’s concepts and themes closely linked to Physical Education, highlighting the influence of liquid modernity on body norms, sporting individualism, commodified leisure, and the social role of dance and play. Acknowledging the complexity of the relationship between Bauman and Physical Education, the study is presented as one possible approach, emphasizing the importance of his theory for understanding the field’s dynamics beyond what is explicitly stated in his writings.Keywords: Zygmunt Bauman. Epistemology. Sociology.